"I'm going to prove you wrong": Responses to perceived discrimination among African American youth. Issue 4 (9th November 2015) - Vega, Desireé; Moore III, James L.; Miranda, Antoinette H.
Abstract : Purpose: – This study aims to explore perceptions of discrimination among ten African American youths as part of a larger qualitative investigation. Design/methodology/approach: – The qualitative methodology utilized the "Prove them Wrong Syndrome" as a theoretical framework. Individual interviews and biographical questionnaires were the primary sources of data collection. Findings: – Four major themes emerged from data analysis: perceived discrimination from others, perceived discrimination from members of one's own racial group, responses to perceived discrimination and buffers against perceived discrimination. Practical implications: – Implications for educators including teachers, school psychologists and school counselors are discussed. Originality/value: – This paper attempted to fill the void in the literature, as it explored the perceptions of discrimination among African American youth, their responses to perceived discrimination and the identification of buffers to compensate for negative experiences with discrimination. Prove them Wrong Syndrome emerged as a major finding in this study as a response to perceived discrimination; nonetheless, it should be further evaluated, as limited research has been conducted in this area. Teachers must be aware of issues students of color may experience at school such as discrimination and how this can harm them emotionally and academically. Moreover, school psychologists and school counselors should be utilized as mental health service providers to combat the potentially negative outcomes of discrimination.